Exhibiting Epistemic Objects - Tybjerg, Karin (Museum and Society, 2018)
Scientific and medical collections contain many of what we may call epistemic objects, i.e. objects that have played important roles in the production of knowledge. Drawing on the work of H.-J. Rheinberger on ‘epistemic things’ and J. Pickstone on ‘ways of knowing’ this paper considers ways of exhibiting epistemic objects that utilize their knowledge-generating potential and allow them to continue to stimulate curiosity and generate knowledge in the exhibition. The epistemic potential of the objects can then be made to work together with the function of the exhibition as a knowledge-generating set-up in its own right. A focus on epistemic history further allows the cultural and scientific roles of objects of science to be combined in exhibitions. This paper takes its point of departure in the development of displays for the exhibition The Body Collected at Medical Museion in Copenhagen, which shows how anatomical specimens have been used to generate medical knowledge. Keywords Epistemic objects, objects of knowledge, scientific instruments, anatomical collections, science as process